The role of discounting in bargaining with private information - Francesc Dilmé (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2023)
In this paper we analyze a continuous-time Coase setting with finite horizon, interdependent values, and different discount rates for the buyer and seller. We fully characterize the equilibrium behavior, which permits us to study how the agents' discount rates (i.e., patience levels) shape the bargaining outcome. We find that the seller's commitment problem persists even when she is fully patient, and that higher seller impatience may lead to higher equilibrium prices. Higher buyer impatience, on the other hand, incentivizes the buyer to trade earlier, which accelerates price decline since the seller's commitment problem is more severe at earlier times. Under appropriate conditions, we conclude that the buyer is better off when he is more impatient, independently of his private valuation; hence, higher bargaining costs may give negotiators with private information greater bargaining power.
Keywords: C78; D82; 330; Bargaining with private information; different discount factors